Comparison of qPCR protocols for quantification of “Candidatus Saccharibacteria”, belonging to the Candidate Phyla Radiation, suggests that 23S rRNA is a better target than 16S rRNA - Papaleo, Stella; Nodari, Riccardo; Sterzi, Lodovico; D’Auria, Enza; Cattaneo, Camilla; Bettoni, Giorgia; Bonaiti, Clara; Pagliarini, Ella; Zuccotti, Gianvincenzo; Panelli, Simona; Comandatore, Francesco (PloS one, 2024)
Candidate Phyla Radiation (CPR) is a large monophyletic group encompassing about 25% of bacterial diversity. Among CPR, "Candidatus Saccharibacteria" is one of the most clinically relevant phyla. Indeed, it is enriched in the oral microbiota of subjects suffering from immune-mediated disorders and it has been found to have immunomodulatory activities. For these reasons, it is crucial to have reliable methods to detect and quantify this bacterial lineage in human samples, including saliva. Four qPCR protocols for quantifying "Ca. Saccharibacteria" (one targeting the 23S rRNA gene and three the 16S) were tested and compared. The efficiency and coverage of these four protocols were evaluated in silico on large genomic datasets, and in vitro on salivary DNA samples, already characterized by amplicon sequencing on the V3-V4 regions of the 16S rRNA. In silico PCR analyses showed that all qPCR primers lose part of the "Ca. Saccharibacteria" genetic variability, even if the 23S qPCR primers matched more lineages than the 16S qPCR primers. In vitro qPCR experiments confirmed that all 16S-based protocols strongly underestimated "Ca. Saccharibacteria" in salivary DNA, while the 23S qPCR protocol gave quantifications more comparable to 16S amplicon sequencing. Overall, our results show that the 23S-based qPCR protocol is more precise than the 16S-based ones in quantifying "Ca. Saccharibacteria", although all protocols probably underestimate specific lineages. These results underline the current limits in quantifying "Ca. Saccharibacteria", highlighting the needs for novel experimental strategies or methods. Indeed, the underestimation of "Ca. Saccharibacteria" in clinical samples could hide its role in human health and in the development of immune-mediated diseases.